Cortical Regions Activated by Spectrally Degraded Speech in Adults With Single Sided Deafness or Bilateral Normal Hearing - Burton, Harold; Reeder, Ruth M.; Holden, Tim; Agato, Alvin; Firszt, Jill B. (Frontiers in Neuroscience, 2021)
Poor speech recognition occurs in single-sided deafness (SSD) from profound sensorineural hearing loss in one ear. Prior studies found adverse sound environments diminished speech intelligibility, inducing greater effort, cognitive loads, fatigue and diminished quality of life in SSD individuals. A possible framework for understanding effortful listening in SSD compared to normal hearing (NH) individuals might be diminished brain activity to spectrally degraded sentences through noise vocoding. We found right ear deaf SSD were significantly less accurate than NH in identifying sentence last words in 8- and 16-band, highly predictable sentences. Accuracies were significantly lower in both groups with 4-band vocoded, less predictable sentences. Group average percent signal changes (BOLD) to these sentences relative to trials of silence were lower in SSD than NH to 4- and 8-band sentences in the left hemisphere (LH). Affected regions included early auditory, association auditory, inferior frontal, premotor, inferior parietal, dorsolateral prefrontal and posterior cingulate cortex. BOLD signal magnitudes were averages from vertices within predefined parcels in surface rendered cortex regions. Parcels with significantly lower amplitude responses in SSD than NH were components of a LH generic language network previously identified as responsible for speech recognition. Multiple parcels from different regions in SSD showed significantly larger signal magnitudes to sentences of greater intelligibility (e.g., 8- or 16- vs 4-band) in all except early auditory and posterior cingulate cortex. Higher sentence predictability rarely evoked significantly higher amplitudes and only in NH. SSD had lower response magnitudes than NH in regions prior studies found responsible for phonetics and phonology of speech, cognitive extraction of meaning, controlled retrieval of word meaning and selection of semantic knowledge. SSD showed no compensatory activity anywhere in the right hemisphere. The findings thus showed deficient activation in a LH fronto-temporo-parietal network that facilitates processing the meaning of words and sentences in context. Diminished activity in affected network parcels might contribute to effortful listening in SSD.